Lithium ion battery

By providing a double-layer positive electrode active material layer and manganese ion adsorbent in the positive electrode of the lithium-ion battery, the performance degradation caused by manganese-based materials during the cycle of the lithium battery is solved, which extends the battery life and improves the performance.

CN119400930APending Publication Date: 2025-02-07SHANGHAI SAIC QINGTAO ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411556815.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Manganese-based materials are likely to lead to capacity attenuation, electrolyte decomposition and battery rate performance limitations during the lithium battery cycle. How to reduce the negative impact of manganese ions on the performance of lithium-ion batteries is an important issue.

Method used

A double-layer positive electrode active material layer is provided in the positive electrode of the lithium-ion battery, and the void ratio of the second positive electrode active material layer is greater than that of the first positive electrode active material layer, and a manganese ion adsorbent is added to the positive electrode to adsorb free manganese ions.

Benefits of technology

By extending the life of lithium batteries, improving their performance, reducing the dissolution and migration of manganese ions, reducing the decomposition of electrolytes, and improving the rate performance and cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a lithium ion battery in the technical field of lithium batteries, in particular to a solid-state lithium ion battery which comprises a positive electrode, the positive electrode comprises a positive electrode current collector, a first positive electrode active material layer and a second positive electrode active material layer, and the porosity of the second positive electrode active material layer is higher than that of the first positive electrode active material layer. The first positive electrode active material layer comprises a spinel manganese oxide and a manganese ion adsorbent, and the second positive electrode active material layer comprises a lithium manganese oxide with a layered structure, a ternary material and a manganese ion adsorbent. Two layers are arranged on the positive electrode, and the porosity of the second positive electrode active material layer is controlled to be larger than that of the first positive electrode active material layer, so that the negative influence of manganese ions can be effectively reduced in the cycle process of the lithium ion battery through the design, the service life of the battery is prolonged, and the performance of the battery is improved; free manganese ions can be effectively adsorbed, and the battery performance is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium ion battery. Background Art

[0002] Manganese ions (Mn 3+ ) is mainly found in positive electrode materials, especially manganese-based positive electrode materials, such as lithium manganese oxide (LiMn2O4) and nickel-cobalt-manganese ternary materials (NCM). The introduction of manganese ions helps to improve the performance of the battery. First, manganese-based positive electrode materials have higher theoretical capacity and energy density, which enables lithium-ion batteries to store more energy. Secondly, manganese is a relatively cheap and abundant element. The use of manganese-based materials can reduce the production cost of the battery. Finally, manganese-based materials have good thermal stability at high temperatures, which can reduce the risk of thermal runaway of the battery, thereby improving the safety of the battery.

[0003] However, manganese-based materials also bring some challenges. For example, manganese-based materials are prone to capacity decay during the cycle of lithium batteries. The main reason is the dissolution and migration of manganese ions, which leads to the destruction of the positive electrode structure. In addition, manganese ions will catalyze the decomposition of electrolytes at high potentials to generate by-products, affecting the cycle life of the battery. At the same time, the electronic and ionic conductivity of manganese-based materials is poor, which limits the rate performance and charge and discharge speed of the battery.

[0004] In summary, how to reduce the negative impact of manganese ions on the performance of lithium-ion batteries is an important issue facing the lithium battery industry. Summary of the invention

[0005] In order to reduce the negative impact of manganese ions on the performance of lithium-ion batteries, the present invention proposes a lithium-ion battery, wherein a double-layer positive electrode active material layer is arranged at the positive electrode, and the porosity of the second positive electrode active material layer is controlled to be greater than that of the first positive electrode active material layer, so as to extend the life of the lithium battery and improve its performance. At the same time, a manganese ion adsorbent is arranged at the positive electrode to effectively adsorb free manganese ions. The technical solution of the present invention is implemented as follows:

[0006] A lithium ion battery comprises a positive electrode, a negative electrode and an electrolyte. The positive electrode comprises a positive electrode current collector, a first positive electrode active material layer and a second positive electrode active material layer. The second positive electrode active material layer has a higher porosity than the first positive electrode active material layer.

[0007] Preferably, the first positive electrode active material layer comprises spinel manganese oxide and a manganese ion adsorbent, and the second positive electrode active material layer comprises a layered lithium manganese oxide, a ternary material and a manganese ion adsorbent.

[0008] Preferably, the spinel manganese oxide has a structural formula of Li 1+b Mn 2-b-c Mc O 4-a Q a , where 0≤a≤1, 0≤b≤0.3 and 0≤c≤1;

[0009] M includes at least one of the following elements: Mg, Al, Ni, Co, Fe, Cr, Cu, Ca, Nb, Mo, Sr, Sb, W, B, Ti, V, Zr, Zn;

[0010] Q includes at least one of the following elements: N, F, S, and Cl.

[0011] Preferably, the layered lithium manganese oxide has a structural formula of aLi2MnO3-(1-a)LiZO2, wherein 0≤a≤1;

[0012] Z includes at least one of the following elements: Al, Mg, Mn, Ni, Co, Cr, V, Fe, Cu, Zn, Ti and B.

[0013] Preferably, the structural formula of the ternary material is LiNi x Co y R z O2, wherein x+y+z=1, R is Mn or Al, 0≤x≤1, 0≤y≤1, 0≤z≤1.

[0014] Preferably, the thickness ratio of the first positive electrode active material layer to the second positive electrode active material layer is (5:1)-(50:1).

[0015] Preferably, the thickness ratio of the first positive electrode active material layer to the second positive electrode active material layer is (10:1)-(20:1).

[0016] Preferably, the manganese ion adsorbent is a resin copolymer.

[0017] Preferably, the resin copolymer comprises at least one of chelating resin CH-90Na, XFS4195 resin, AmberlitelRC748, LonacSR-5, PuroliteS-930, Chelex100, D851, diethylbenzene cross-linked poly-4-vinylpyridine and D402-II.

[0018] Preferably, the lithium-ion battery is a solid-state lithium-ion battery, comprising a positive electrode, a negative electrode and a solid electrolyte; the solid electrolyte is located between the positive electrode and the negative electrode.

[0019] The present invention proposes an innovative lithium-ion battery design, which prolongs the life of the lithium battery and improves its performance by setting a double-layer active material layer in the positive electrode plate and controlling the porosity of the second positive electrode active material layer to be greater than that of the first positive electrode active material layer. Since the lithium-rich manganese and ternary materials will be deactivated before lithium manganate, in an ideal case, when lithium manganate reaches the performance inflection point, the lithium-rich manganese and ternary materials are both deactivated. At this time, the second positive electrode active material layer exists as a protective layer. In addition, a manganese ion adsorbent is provided in the positive electrode plate to adsorb manganese ions released during the circulation of lithium manganate. The porosity of the second positive electrode active material layer is greater than that of the first positive electrode active material layer, so that the electrolyte can better infiltrate the positive electrode, thereby prolonging the life of the lithium battery and improving its performance. DETAILED DESCRIPTION

[0020] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specific implementation methods are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the specification and claims of the present invention and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0022] In the description of the specific implementation methods of the present invention, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present invention, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0023] Reference to "embodiments" in the present invention means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in the present invention may be combined with other embodiments.

[0024] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in the present invention generally indicates that the associated objects before and after are in an "or" relationship.

[0025] Throughout the present invention, numerical values ​​represent approximate measures or limits of ranges to cover minor deviations from given values ​​as well as embodiments with about the values ​​mentioned and embodiments with the exact values ​​mentioned. Except for the working examples provided at the end of the detailed description, all numerical values ​​of parameters (e.g., amounts or conditions) in this specification (including the appended claims) should be understood to be modified by the term "about" in all cases, regardless of whether "about" actually appears before the numerical value. "About" indicates that the stated numerical value allows some minor imprecision (close to the exact value of the value to some extent; approximately or reasonably close to the value; almost). If the imprecision provided by "about" is not otherwise understood in this ordinary sense in the art, "about" as used in the present invention at least indicates the variation that can be produced by the ordinary methods of measuring and using such parameters. For example, "about" may include a variation of less than or equal to 5%, optionally less than or equal to 4%, optionally less than or equal to 3%, optionally less than or equal to 2%, optionally less than or equal to 1%, optionally less than or equal to 0.5%, and in some aspects, optionally less than or equal to 0.1%.

[0026] Additionally, disclosure of ranges includes disclosure of all values ​​within the entire range and further divided ranges, including endpoints and sub-ranges given for such ranges.

[0027] The positive electrode material of manganese-based lithium-ion batteries usually uses spinel-structured LiMn2O4. During the charge and discharge process, lithium ions are embedded and de-embedded between the positive and negative electrodes, accompanied by the redox reaction of manganese ions. Specifically, during the charge process, lithium ions are de-embedded from the LiMn2O4 positive electrode, and manganese ions are de-embedded from the Mn 3+ Oxidized to Mn 4+ During discharge, lithium ions are re-embedded into the positive electrode, and manganese ions are transferred from Mn 4+ Reduction to Mn 3+ This redox reaction provides the electrochemical energy of the battery. However, the redox reaction of manganese ions can also cause some problems, leading to a decrease in battery performance. For example, Mn 3+ Ions are prone to disproportionation reaction in the electrolyte to generate Mn 2+ and Mn 4+ , where Mn 2+It will dissolve into the electrolyte, migrate to the negative electrode and deposit on the surface of the negative electrode to form manganese deposits. These deposits will affect the electrochemical properties of the negative electrode and cause the battery capacity to decay.

[0028] In order to solve the above problems, the present invention proposes a lithium-ion battery, including a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode includes a positive electrode current collector, a first positive electrode active material layer and a second positive electrode active material layer, and the positive electrode current collector is used to collect and conduct current. Usually made of aluminum foil, the first positive electrode active material layer is a layer of material directly coated on the positive electrode current collector, which is mainly responsible for the electrochemical reaction of the battery. It is usually made of materials such as lithium metal oxide, and the second positive electrode active material layer is located on the first positive electrode active material layer to further enhance the performance of the battery.

[0029] In some embodiments, the porosity of the second positive electrode active material layer is higher than that of the first positive electrode active material layer, which enables the electrolyte in the lithium-ion battery to better infiltrate the positive electrode, thereby improving the performance of the battery.

[0030] In some embodiments, the first positive electrode active material layer includes spinel manganese oxide and a manganese ion adsorbent, and the second positive electrode active material layer includes a layered lithium manganese oxide, a ternary material and a manganese ion adsorbent, wherein the spinel structure of the spinel manganese oxide provides good ion conductivity and structural stability, the manganese ion adsorbent is used to capture and fix manganese ions to prevent them from dissolving and migrating during the battery cycle, the layered lithium manganese oxide facilitates the embedding and extraction of lithium ions, and the ternary material has high energy density and good thermal stability, and is widely used in high-performance lithium-ion batteries.

[0031] In some embodiments, the spinel manganese oxide has a structural formula of Li (1+b) Mn 2-b-c M c O 4-a Q a , wherein 0≤a≤1, 0≤b≤0.3 and 0≤c≤1, M includes at least one of the following elements: Mg, Al, Ni, Co, Fe, Cr, Cu, Ca, Nb, Mo, Sr, Sb, W, B, Ti, V, Zr and Zn, and Q includes at least one of the following elements: N, F, S, and Cl.

[0032] In some embodiments, the layered lithium manganese oxide has a structural formula of xLi2MnO3-(1-a)LiZO2, wherein 0≤a≤1, and Z includes at least one of the following elements: Al, Mg, Mn, Ni, Co, Cr, V, Fe, Cu, Zn, Ti, and B.

[0033] In some embodiments, the structural formula of the ternary material is LiNix Co y R z O2, wherein x+y+z=1, R is Mn or Al, 0≤x≤1, 0≤y≤1, 0≤z≤1.

[0034] In some embodiments, a thickness ratio of the first positive electrode active material layer to the second positive electrode active material layer is (5:1)-(50:1).

[0035] In practical applications, the thickness ratio of the first positive electrode active material layer to the second positive electrode active material layer can be selected from: 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1, 21:1, 22:1, 23:1, 24:1 1, 25:1, 26:1, 27:1, 28:1, 29:1, 30:1, 31:1, 32:1, 33:1, 34:1, 35:1, 36:1, 37:1, 38:1, 39:1, 40:1, 41:1, 42:1, 43:1, 44:1, 45:1, 46:1, 47:1, 48:1, 49:1, 50:1. The above are only examples and are not limiting.

[0036] In some preferred embodiments, the thickness ratio of the first positive electrode active material layer to the second positive electrode active material layer is (10:1)-(20:1).

[0037] In practical applications, the thickness ratio of the first positive electrode active material layer to the second positive electrode active material layer may be: 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1. The above is only an example and is not limiting.

[0038] Different thicknesses of positive electrode active material layers can optimize the electrochemical performance of the battery. A thicker first positive electrode active material layer can provide higher capacity, while a thinner second positive electrode active material layer can improve the rate performance and cycle life of the battery. Secondly, different thicknesses of positive electrode active material layers can improve the mechanical stability of the battery. A thicker first positive electrode active material layer can provide better structural support, while a thinner second positive electrode active material layer can reduce the expansion and contraction of the electrode material, thereby improving the cycle stability of the battery.

[0039] In some embodiments, the manganese ion adsorbent is a resin copolymer, including one or two or more polymers selected from chelating resin CH-90Na, XFS4195 resin, AmberlitelRC748, LonacSR-5, PuroliteS-930, Chelex100, D851, diethylbenzene cross-linked poly-4-vinylpyridine ((C10-H10.C7-H7-N)x) and D402-Ⅱ. The above-mentioned resin copolymer contains functional groups that can form stable chelates with manganese ions. These groups form multidentate coordination with manganese ions to firmly bind manganese ions to the resin. Secondly, these resins usually have a porous structure, which provides a large amount of surface area and adsorption sites, which helps to improve the adsorption efficiency. These mechanisms work together to enable these resin copolymers to effectively adsorb manganese ions.

[0040] It is understood that, whether it is the first positive electrode active material layer or the second positive electrode active material layer, optionally, the positive electrode active material in the positive electrode can be doped with one or more conductive agents providing electronic conduction and / or at least one polymer binder material that improves the structural integrity of the positive electrode. For example, optionally, the positive electrode active material can be mixed with a binder such as poly (tetrafluoroethylene) (PTFE), sodium carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), polyvinylidene fluoride (PVDF), nitrile rubber (NBR), styrene ethylene butylene styrene copolymer (SEBS), styrene butadiene styrene copolymer (SBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), sodium alginate, lithium alginate and combinations thereof. The conductive agent may include carbon-based materials, powdered nickel or other metal particles or conductive polymers. Carbon-based materials may include particles such as carbon black, graphite, superP, acetylene black (such as, KETCHENTM black or DENKATM black), carbon fibers and nanotubes, graphene, and the like. Examples of the conductive polymer include polyaniline, polythiophene, polyacetylene, polypyrrole, poly(3,4-ethylenedioxythiophene) polystyrene sulfonate, and the like.

[0041] The first positive electrode active material layer and the second positive electrode active material layer may independently include greater than or equal to about 50 weight % to less than or equal to about 97 weight % of the positive electrode active material, optionally greater than or equal to about 0 weight % to less than or equal to about 60 weight % of the solid electrolyte, optionally greater than or equal to about 0 weight % to less than or equal to about 15 weight % of the conductive agent, and optionally greater than or equal to about 0 weight % to less than or equal to about 10 weight % of the binder.

[0042] Preferably, the lithium ion battery is a solid-state lithium ion battery, and the electrolyte may be a solid electrolyte. The solid electrolyte may include one or more solid electrolyte particles, and the solid electrolyte particles may preferably include one or more polymer components, oxide particles, sulfide particles, halide particles, borate particles, nitride particles or hydride particles. When polymer particles are used, lithium salts may be used for review. As an embodiment, the polymer-based component may include one or more polymer materials selected from the group including the following: polyethylene glycol, polyethylene oxide (PEO), poly (p-phenylene ether) (PPO), poly (methyl methacrylate) (PMMA), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polyvinylidene fluoride co-hexafluoropropylene (PVDF-HFP), polyvinyl chloride (PVC) and combinations thereof. In one variation, one or more polymer materials may have a carbon content equal to about 10 -4 S / cm ionic conductivity.

[0043] As an embodiment, the oxide particles may include one or more garnet ceramics, LISICON type oxides, NASICON type oxides and perovskite type ceramics. For example, the one or more garnet ceramics may be selected from the group consisting of: Li 6.5 LqCy 1.75 Te 0.25 O 12 、Li7La3Zr2O 12 , Li 6.2 Ga 0.3 La 2.95 R 0.05 Zr2O 12 , Li 6.85 La 2.9 Ca 0.1 Zr 1.75 Nb 0.25 O 12 , Li 6.25 Al 0.25 La3Zr2O 12 , Li 6.75 LqCy 1.75 Nb 0.25 O 12 , Li 6.75 LqCy 1.75 Nb 0.25 O 12 and their combinations.

[0044] The one or more LISICON type oxides may be selected from the group comprising: Li 14 Zn(GeO4)4、Li 3+x (P 1-x Si x )O4 (where 0 < x < 1), Li 3+x Ge x V 1-x O4 (where 0 < x < 1) and combinations thereof. One or more NASICON-type oxides may be defined by LiMM′(PO4)3, where M and M′ are independently selected from Al, Ge, Ti, Sn, Hf, Zr, and La. For example, in certain variations, one or more NASICON-type oxides may be selected from the group consisting of: Li 1+x Al x Ge 2-x (PO4)3 (LAGP) (where 0 ≤ x ≤ 2), Li 1+x Al x Ti 2-x (PO4)3 (LATP) (where 0 ≤ x ≤ 2), Li 1+x Y x Zr 2-x (PO4)3 (LYZP) (where 0 ≤ x ≤ 2), Li 1.3 Al 0.3 Ti 1.7 (PO4)3, LiTi2(PO4)3, LiGeTi(PO4)3, LiGe2(PO4)3, LiHf2(PO4)3, and combinations thereof. One or more perovskite-type ceramics may be selected from the group consisting of: Li 3.3 La 0.53 TiO3, LiSr 1.65 Zr 1.3 Ta 1.7 O9, Li 2x-y Sr 1-x Ta y Zr 1-y O3 (where x = 0.75y and 0.60 < y < 0.75), Li 3 / 8 Sr 7 / 16 Nb 3 / 4Zr 1 / 4 O3, Li 3x La (2 / 3-x) TiO3 (where 0 < x < 0.25) and combinations thereof. In one variation, one or more oxide-based materials may have an ionic conductivity greater than or equal to about 10 -5 S / cm to less than or equal to about 10 -1 S / cm.

[0045] As one embodiment, the sulfide-based particles may include one or more sulfide-based materials selected from the group consisting of: Li2S-P2S5, Li2S-P2S5-MSx (where M is Si, Ge and Sn and 0≤x≤2), Li 3.4 Si 0.4 P 0.6 S4, Li 10 GeP2S 11.7 O 0.3 , Li 9.6 P3S 12 、Li7P3S 11 、Li9P3S9O3、Li 10.35 Si 1.35 P 1.65 S 12 , Li 9.81 Sn 0.81 P 2.19 S 12 , Li 10 (Si 0.5 Ge 0.5 )P2S 12 、Li(Ge 0.5 Sn 0.5 )P2S 12 、Li(Si 0.5 Sn 0.5 )PsS 12 , Li 10 GeP2S 12 (LGPS), Li6PS5X (where X is Cl, Br or I), Li7P2S8I, Li 10.35 Ge 1.35 P 1.65 S 12 , Li 3.25 Ge 0.25 P 0.75 S4, Li 10 SnP2S 12 , Li 10 SiP2S 12 , Li 9.54 Si 1.74 P 1.44 S 11.7 C l0.3 , (1-x) P2S 5-x Li2S (where 0.5≤x≤0.7) and combinations thereof. In one variation, one or more sulfide-based materials may have a carbon content greater than or equal to about 10 -7 S / cm to an ionic conductivity of less than or equal to about 1 S / cm.

[0046] As an embodiment, the halide-based particles may include one or more halide-based materials selected from the group consisting of: Li2CdC l4, Li2MgC l4 , Li2Cd I4 , Li2ZnI4, Li3OCl, LiI, Li5ZnI4, Li3OCl 1- x Br x (where 0 < x < 1) and combinations thereof. In one variation, one or more halide-based materials may have an ionic conductivity greater than or equal to about 10 -8 S / cm to less than or equal to about 10 -1 S / cm.

[0047] As one embodiment, the borate-based particles may include one or more borate-based materials selected from the group consisting of: Li2B4O7, Li2O-(B2O3)-(P2O5), and combinations thereof. In one variation, one or more borate-based materials may have an ionic conductivity greater than or equal to about 10 -7 S / cm to less than or equal to about 10 -2 S / cm.

[0048] As one embodiment, the nitride-based particles may include one or more nitride-based materials selected from the group consisting of: Li3N, Li7PN4, LiSi2N3, LiPON, and combinations thereof. In one variation, one or more nitride-based materials may have an ionic conductivity greater than or equal to about 10 -9 S / cm to less than or equal to about 1 S / cm.

[0049] As one embodiment, the hydride-based particles may include one or more hydride-based materials selected from the group consisting of: Li3AlH6, LiBH4, LiBH4-LiX (where X is one of Cl, Br, and I), LiNH2, Li2NH, LiBH4-LiNH2, and combinations thereof. In one variation, one or more hydride-based materials may have an ionic conductivity greater than or equal to about 10 -7 S / cm to less than or equal to about 10 -2 S / cm.

[0050] It should be noted that the "one or more" claimed in the present invention refers to the types of resin copolymers that those skilled in the art can selectively choose according to actual needs and factors such as the price of raw materials. Whether it is one, two, or even more, it does not change its function and effect of being able to adsorb manganese ions. Since this part of the technology is prior art, the present invention only exemplifies rather than limits the types of these materials. In actual applications, materials with the same or similar properties as the above materials can also be selected as manganese ion adsorbents.

[0051] The embodiments of the present invention will be described in more detail below through examples and comparative examples. It should be noted that the embodiments of the present invention are not limited to these examples.

[0052] Example 1

[0053] A lithium-ion battery comprises a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises a positive electrode current collector, a first positive electrode active material layer and a second positive electrode active material layer, the negative electrode and the electrolyte are conventional materials, and the material selection method of the positive electrode is as follows:

[0054] 1. The first positive electrode active material layer structure is composed of Li2Mn2O4 (96%) + super-P (2%) + PVDF (2%).

[0055] 2. The second positive electrode active material layer structure is composed of NCM333 (96%) + lithium-rich manganese (35.2%) + super-P (2wt%) + PVDF (2wt%) + adsorption resin (0.8%), the adsorption resin is divinylbenzene cross-linked poly-4-vinylpyridine ((C10-H10.C7-H7-N)x, wherein divinylbenzene accounts for 2wt% of the resin, and the porosity of the second positive electrode active material layer is 20%

[0056] 3. The thickness ratio of the first positive electrode active material layer to the second positive electrode active material layer is 10:1.

[0057] The positive electrode, negative electrode and electrolyte of the above-mentioned lithium battery are all prepared by conventional techniques.

[0058] Example 2

[0059] A lithium-ion battery comprises a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises a positive electrode current collector, a first positive electrode active material layer and a second positive electrode active material layer, the negative electrode and the electrolyte are conventional materials, and the material selection method of the positive electrode is as follows:

[0060] 4. The first positive electrode active material layer structure consists of Li2Mn2O4 (96%) + super-P (2%) + PVDF (2%).

[0061] 5. The second positive electrode active material layer structure is composed of NCM622 (50%) + lithium-rich manganese (35.2%) + super-P (2wt%) + PVDF (2wt%) + adsorption resin (0.8%), the adsorption resin is divinylbenzene cross-linked poly-4-vinylpyridine ((C10-H10.C7-H7-N)x, wherein divinylbenzene accounts for 2wt% of the resin, and the porosity of the second positive electrode active material layer is 30%

[0062] 6. The thickness ratio of the first positive electrode active material layer to the second positive electrode active material layer is 10:1.

[0063] The positive electrode, negative electrode and electrolyte of the above-mentioned lithium battery are all prepared by conventional techniques.

[0064] Example 3

[0065] A lithium-ion battery comprises a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises a positive electrode current collector, a first positive electrode active material layer and a second positive electrode active material layer, the negative electrode and the electrolyte are conventional materials, and the material selection method of the positive electrode is as follows:

[0066] 1. The first positive electrode active material layer structure is composed of Li2Mn2O4 (96%) + super-P (2%) + PVDF (2%).

[0067] 2. The second positive electrode active material layer structure is composed of NCM333 (50%) + lithium-rich manganese (36%) + super-P (2wt%) + PVDF (2wt%), and the adsorption resin is divinylbenzene cross-linked poly-4-vinylpyridine ((C10-H10.C7-H7-N)x, in which divinylbenzene accounts for 2wt% of the resin, and the porosity of the second positive electrode active material layer is 20%

[0068] 3. The thickness ratio of the first positive electrode active material layer to the second positive electrode active material layer is 10:1.

[0069] The positive electrode, negative electrode and electrolyte of the above-mentioned lithium battery are prepared by conventional technology.

[0070] Comparative Example

[0071] A lithium-ion battery comprises a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode and the electrolyte are conventional materials, and the positive electrode is selected as follows:

[0072] The positive electrode structure is composed of Li2Mn2O4 (75.2%) + NCM622 (10%) + lithium-rich manganese (10%) + super-P (2%) + PVDF (2wt%), and the adsorption resin is poly-4-vinylpyridine ((C10-H10.C7-H7-N)x cross-linked with divinylbenzene, wherein divinylbenzene accounts for 2wt% of the resin.

[0073] The positive electrode, negative electrode and electrolyte of the above-mentioned lithium battery are all prepared by conventional techniques.

[0074] Examples 1-3 were selected to conduct performance test comparison with the comparative example.

[0075] The testing process is as follows:

[0076] 1. 45℃ cycle test method: In a 45℃ constant temperature box, charge to 4.2V at 1C, charge to 0.05C at constant voltage, and then discharge to 3.0V at 1C. Stop the test when the capacity retention rate reaches 80%.

[0077] 2. Test method for negative electrode Mn element: Weigh about 0.1g powder (accurate to ±0.0003g) of two negative electrode sheets after the cycle is completed, place them in a 100ml beaker, add a small amount of distilled water to wet the bottom of the cup, then add 5ml (12mol / L) HC to dissolve, heat on an electric heating plate for 20min, remove and cool, and dilute for testing. Introduce the prepared series of standard solutions into an inductively coupled plasma spectrometer (ICP) instrument, and measure the intensity of each element in the standard solution at the wavelength of the manganese element to be tested. When the linear correlation coefficient of the working curve r≥0.9995, the test can be carried out.

[0078] Take four groups of samples in total, including Examples 1-3 and Comparative Examples, with 10 samples in each group. All samples are tested, and the test result data are averaged.

[0079] The final test results are shown in the following table:

[0080]

[0081] Compared with Example 1, Example 2 increases the porosity of the second positive electrode active material layer, improves the battery cycle performance by 16.8%, and reduces the manganese ion element deposited on the negative electrode by 3.1%.

[0082] Compared with Example 1, Example 3 cancels the addition of adsorption resin, reduces the battery cycle performance by 18.6%, and at the same time, the manganese ion element deposited on the negative electrode increases by 65.7%, indicating that the adsorption resin helps to improve the cycle performance of the lithium battery.

[0083] Compared with Example 1, the comparative example cancels the stratification of the first positive electrode active material layer and the second positive electrode active material layer, reduces the battery cycle performance by 27.9%, and at the same time, the manganese ion element deposited on the negative electrode increases by 98.3%.

[0084] According to the above table, the present invention realizes the adsorption of manganese ions by arranging a manganese ion adsorbent at the positive electrode, and controls the porosity of the second positive electrode active material layer to be greater than that of the first positive electrode active material layer, thereby greatly improving the battery cycle performance during the lithium ion battery cycle.

[0085] It should be pointed out that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A lithium ion battery comprising a positive electrode, a negative electrode and an electrolyte, characterized in that: The positive electrode includes a positive electrode current collector, a first positive electrode active material layer and a second positive electrode active material layer, wherein the second positive electrode active material layer has a higher porosity than the first positive electrode active material layer.

2. The lithium-ion battery according to claim 1, characterized in that The first positive electrode active material layer includes spinel manganese oxide and a manganese ion adsorbent, and the second positive electrode active material layer includes layered lithium manganese oxide, a ternary material and a manganese ion adsorbent.

3. The lithium-ion battery according to claim 2, characterized in that: The spinel manganese oxide has a structural formula of Li 1+ b Mn 2-b-c M c O 4-a Q a , where 0≤a≤1, 0≤b≤0.3 and 0≤c≤1; M includes at least one of the following elements: Mg, Al, Ni, Co, Fe, Cr, Cu, Ca, Nb, Mo, Sr, Sb, W, B, Ti, V, Zr, Zn; Q includes at least one of the following elements: N, F, S, and Cl.

4. The lithium-ion battery according to claim 2, characterized in that: The structural formula of the layered lithium manganese oxide is aLi2MnO3-(1-a)LiZO2, wherein 0≤a≤1; Z includes at least one of the following elements: Al, Mg, Mn, Ni, Co, Cr, V, Fe, Cu, Zn, Ti and B.

5. The lithium-ion battery according to claim 2, characterized in that: The structural formula of the ternary material is LiNi x Co y R z O2, wherein x+y+z=1, R is Mn or Al, 0≤x≤1, 0≤y≤1, 0≤z≤1.

6. The lithium-ion battery according to claim 2, characterized in that: The thickness ratio of the first positive electrode active material layer to the second positive electrode active material layer is (5:1)-(50:1).

7. The lithium-ion battery according to claim 6, characterized in that: The thickness ratio of the first positive electrode active material layer to the second positive electrode active material layer is (10:1)-(20:1).

8. The lithium-ion battery according to claims 1-7, characterized in that: The manganese ion adsorbent is a resin copolymer.

9. The lithium-ion battery according to claim 8, characterized in that: The resin copolymer includes at least one of chelating resin CH-90Na, XFS4195 resin, AmberlitelRC748, LonacSR-5, PuroliteS-930, Chelex100, D851, poly-4-vinylpyridine cross-linked with diethylbenzene and D402-II.

10. The lithium-ion battery according to claim 9, characterized in that: The lithium ion battery is a solid-state lithium ion battery, comprising a positive electrode, a negative electrode and a solid electrolyte; the solid electrolyte is located between the positive electrode and the negative electrode.